Susceptibility of Oral Bacteria to Antimicrobial Agents and Virulence Factors - Ali, Muna Jalal; Makky, Essam A.; Batool, Tahira; M. M., Yusoff (JOCPR, 2015)
Tooth decay is considered the most widespread infectious disease in the world. This study aims to isolate and identify the important bacteria related to tooth decay, determine the sensitivity of bacteria in certain types of antimicrobial agents, and study the effect of heavy metals on bacterial isolates. A total of 50 swabs were collected from the mouths of patients from both sexes, with ages ranging from 1–60 years. The patients were advised to consult with dental clinics and specialized centers to isolate and identify the causative agents associated with oral diseases. Results showed that infection rates in younger age groups (1–20 and 20–40) are higher than the elder group (40–60), with percent incidence of 44% and 32%, respectively. Antibiotic sensitivity test against the isolates showed that chloramphenicol had the highest sensitivity effect with 83.2% followed by rifampicin and gentamicin with 81.35%, penicillin G with 64.40%, and streptomycin with 16.94%. In addition, 100% resistance was recorded against seven heavy metals, including silver nitrate, iron chloride, zinc chloride, and lead acetate. The sensitivity to mercury, cadmium, and copper sulfate were 100%, 86.44%, and 1.69%, respectively. Hemolysin had the highest ability to produce virulence factors (72.88%), followed by lecithinase (42.37%) and protease (25.42%). Lipase and urease had the lowest virulence factor production (10.16%).